Postrzeganie przez rodziców możliwości wykorzystania sztucznej inteligencji w edukacji i wychowaniu dzieci. Wyniki badań własnych - Nazaruk, Stanisława Katarzyna; Rybka, Anna; Mościbrodzka, Julia; Sokołowska, Barbara (Studia Edukacyjne, 2025)
In the era of a dynamic development of technology, artificial intelligence has ceased to be solely a subject of research and has become a major factor impacting social, economic and educational reality. Therefore, a study was undertaken to examine parents’ attitudes towards the use of artificial intelligence in the education and upbringing of children. A survey-type research was conducted among 162 parents raising children attending grades 1-3 from several primary schools in Lubelskie Voivodeship. The main research problem was formulated as the question: How do parents perceive the use of artificial intelligence in the education and upbringing of children? The results of the study showed that respondents perceive both benefits and dangers related to the use of artificial intelligence in education. In contrast, they leave the area of parenting outside the influence of AI algorithms.